Stem cell-derived exosome treatment for acute spinal cord injury: a systematic review and meta-analysis based on preclinical evidence - Chunlin Mou; Ziyao Xia; Ziyao Xia; Ziyao Xia; Xiujuan Wang; Xunan Dai; Jiaxian Wang; Chun Zhang; Chun Zhang; Yongsheng Xu; Yongsheng Xu; Yongsheng Xu (Frontiers in Neurology)
BackgroundThe study aims were to systematically review and analyze preclinical research on the efficacy of exosomes derived from various mesenchymal stem cell sources (MSC-exos) for the treatment of spinal cord contusion injury (SCI) in small animal models.MethodsWe conducted a systematic search of PubMed, Embase and Google Scholar databases from their inception through February 29, 2024, to identify eligible English-language studies based on predefined inclusion and exclusion criteria. Two independent investigators performed literature screening, data extraction and bias assessment.ResultsA total of 235 rats were used to assess locomotor recovery at the initial assessment, and exhibited significant improvement in hind limb movement in those treated with exosomes, as indicated by a statistically significant increase in Basso-Beattie-Bresnahan (BBB) scores (MD: 1.26, 95% CI: 1.14–1.38, p < 0.01) compared to the controls. This trend persisted in final assessment data across 21 studies, with pooled analysis confirming similar results (MD: 1.56, 95% CI: 1.43–1.68, p < 0.01). Funnel plot analysis indicated asymmetry in the pooled BBB scores at both baseline and endpoint assessments, suggesting potential publication bias. Exosomes were derived from bone marrow, adipose tissue, umbilical cord or human placental MSCs. Meta-analysis results showed no statistically significant differences in therapeutic efficacy among these MSC-exos sources at various treatment time points.ConclusionMSC-exos demonstrated considerable promise in improving motor function in SCI-affected rats, with bone marrow MSC-derived exosomes having particularly notable effectiveness.